Case Report: Aggressive neural crest tumors in a child with familial von Hippel Lindau syndrome associated with a germline VHL mutation (c.414A>G) and a novel KIF1B gene mutation - Landen, Lucie; De Leener, Anne; Le Roux, Manon; Brichard, Bénédicte; Aydin, Selda; Maiter, Dominique; Lysy, Philippe A. (Frontiers in Endocrinology, 2023)
Introduction Von Hippel Lindau (VHL) syndrome is caused by an autosomal dominant hereditary or sporadic germline mutation of the VHL gene with more than five hundred pathogenic mutations identified. Pheochromocytomas and rarely paragangliomas occur in 10-50% of patients with VHL syndrome usually around 30 years of age and exceptionally before the age of 10. Case presentation We diagnosed a 9-year-old girl of normal appearance and severe refractory hypertension, with a norepinephrine-secreting pheochromocytoma related to VHL syndrome due to a known familial germline heterozygous mutation of VHL gene (c.414A>G), also present in three members of her family. At age 13, a pelvic tumor and a left adrenal pheochromocytoma that showed to be multi-metastatic to both lungs were discovered in the patient leading to left adrenalectomy and pelvic tumor resection. In addition to the germline VHL gene mutation, blood analysis using Next Generation Sequencing identified a novel heterozygous germline mutation of the KIF1B gene (c.3331_3332del; p.Asn1111Glnfs*21), which is only present in the girl and not the other family members. The patient is currently under steroid substitution therapy and leads a normal life. Discussion This family is notable by the early age of onset of multiple neural crest tumors associated with a high propensity for malignancy and metastatic spread. Most reports in the literature associated the VHL mutation with a later onset in adulthood and a benign course, which contrast with our findings and question the role of this mutation in the phenotype expressed in this kindred. Also, the presence of concomitant mutations in two susceptibility genes for neural crest tumors poses the question of their respective roles in the development of tumors in this family. Our familial case description illustrates the potential for systematic use of targeted Next Generation Sequencing with multi-gene panels in patients with neural crest tumors to confirm the role of known susceptibility genes as well as identifying new ones, but also to contribute to comprehensive databases on gene variants and their phenotypic counterparts in this specific area of medicine.